Intrinsic properties and synaptic connectivity of Phox2b-expressing neurons in rat rostral parvocellular reticular formation. (May 2022) - Kajiwara, Risa; Nakamura, Shiro; Ikeda, Keiko; Onimaru, Hiroshi; Yoshida, Atsushi; Tsutsumi, Yumi; Nakayama, Kiyomi; Mochizuki, Ayako; Dantsuji, Masanori; Nishimura, Akiko; Tachikawa, Satoshi; Iijima, Takehiko; et al.
Highlights: Most Phox2b + rPCRt neurons were glutamatergic, but not GABAergic/glycinergic. The firing characteristics differ between Phox2b + neurons in the rPCRt and RdV. About half of Phox2b + rPCRt neurons received inputs from the RdV. Some Phox2b + rPCRt neurons directly projected to the trigeminal motor nucleus. Phox2b + rPCRt neurons may contribute to feeding behavior. Abstract: The paired-like homeobox 2b gene ( Phox2b ) is critical for the development of the autonomic nervous system. We have previously demonstrated the distinct characteristics of Phox2b -expressing (Phox2b + ) neurons in the reticular formation dorsal to the trigeminal motor nucleus (RdV), which are likely related to jaw movement regulation. In this study, we focused on Phox2b + neurons in the rostral parvocellular reticular formation (rPCRt), a critical region for controlling orofacial functions, using 2–11-day-old Phox2b -EYFP rats. Most Phox2b + rPCRt neurons were glutamatergic, but not GABAergic or glycinergic. Approximately 65 % of Phox2b + rPCRt neurons fired at a low frequency, and approximately 24 % of Phox2b + rPCRt neurons fired spontaneously, as opposed to Phox2b + RdV neurons. Stimulation of the RdV evoked inward postsynaptic currents in more than 50 % of Phox2b + rPCRt neurons, while only one Phox2b + rPCRt neuron responded to stimulation of the nucleus of the solitary tract. Five of the 10 Phox2b + neurons sent their axons that ramified within the trigeminal motor nucleus (MoV). Of these, the axons of the two neurons terminated within both the MoV and rPCRt. Our findings suggest that Phox2b + rPCRt neurons have distinct electrophysiological and synaptic properties that may be involved in the motor control of feeding behavior.